Efektivitas pemupukan N, P, K dan Mg atas estimasi kebutuhan unsur hara makro untuk tanaman sawi hijau akuaponik - Rahmah Hayati; Muhammad Irzan Majid; Erwin Masrul Harahap (Composite : Jurnal Ilmu Pertanian, 2023)
Brassica juncea L. was know as mustard vegetable that has higher an economic value. However, it was a cultivation depend on the estimation of fertilizer application to increase to crop production. This study determine to nutrients obtained the optimal production results. Furthermore, the method used a survey method or qualitative research. Whereas, the conventional planting experimental design with a spacing of 20 × 20 cm per plant in 1 hectare. The percentage of N was calculated using the Kjeldahl method. Then, the compound of P, K, and Mg used a spectrophotometry. The data was analyzed using Microsoft Excel 2019. For parameters observed i.e: the wet weight (gr) and dry weight (gr), dry basis or Md (%), percentage from N, P, K, and Mg. Needed for total fertilizer to 10 tons/ha until 40 tons/ha. The results showed that fertilizer N was found in 3.86%, P was calculate in 0.72%, K was obtain in 3.83% and Mg was found in 0.37%. Furthermore, it was the average weight of Brassica juncea L. was 91.01 gr, wherein the dry weight was found in 6.72 gr. The dry basis Md was 12.54%. Finally, the fertilizer recommendations for Brassica juncea L. plants to optimal results up to 40 tons/ha using the fertilizer 5.45 grams. In this case, to the total urea in fertilization was 2.5 grams, and SP-36 fertilizer was 0.6 grams. Then, the KCl fertilizer was 1.8 grams, and dolomite of 0.6 grams with a recommended planting doses to aquaphonic system.